The impact of creativity on functional outcome in schizophrenia: a mediational model - Agurne Sampedro (Nature Portfolio, 2021)
Abstract Functional impairment remains one of the most challenging issues for treatment in schizophrenia. However, previous studies have mainly focused on the negative impact of symptoms excluding variables that could positively impact functional outcome, such as creativity, which is considered an adaptive capacity for real-life problem-solving. This study analyzed the predictive role of creativity on functional outcome in 96 patients with schizophrenia through a mediational model, including sociodemographic, clinical, neurocognitive, and social cognitive variables. Path analysis revealed that creativity significantly mediated the relationship between neurocognition and functional outcome, and that creativity mediated between negative symptoms and functional outcome. Additionally, neurocognition was directly associated with functional outcome and social functioning was associated with creativity. The involvement of creativity in functional outcome could have relevant implications for the development of new interventions. These findings open up a new field of research on additional personal resources as possible factors of functional outcome in schizophrenia and other diseases.